CXCR4 and CXCR7 Signaling Pathways: A Focus on the Cross-Talk Between Cancer Cells and Tumor Microenvironment - Santagata, Sara; Ieranò, Caterina; Trotta, Anna Maria; Capiluongo, Anna; Auletta, Federica; Guardascione, Giuseppe; Scala, Stefania (Frontiers in Oncology, 2021)
The chemokine receptor 4 (CXCR4) and 7 (CXCR7) are G-protein-coupled receptors (GPCRs) activated through their shared ligand CXCL12 in multiple human cancers. They play a key role in the tumor/tumor microenvironment (TME) promoting tumor progression, targeting cell proliferation and migration, while orchestrating the recruitment of immune and stromal cells within the TME. CXCL12 excludes T cells from TME through a concentration gradient that inhibits immunoactive cells access and promotes tumor vascularization. Thus, dual CXCR4/CXCR7 inhibition will target different cancer components. CXCR4/CXCR7 antagonism should prevent the development of metastases by interfering with tumor cell growth, migration and chemotaxis and favoring the frequency of T cells in TME. Herein, we discuss the current understanding on the role of CXCL12/CXCR4/CXCR7 cross-talk in tumor progression and immune cells recruitment providing support for a combined CXCR4/CXCR7 targeting therapy. In addition, we consider emerging approaches that coordinately target both immune checkpoints and CXCL12/CXCR4/CXCR7 axis.